Studi Tentang Peranan Online Game pada Peningkatan Kemampuan Pemecahan Masalah Matematika - Ilham Falani; Rina Nurhidayati (Universitas Mathla'ul Anwar Banten, 2021)
The purpose of this study was to study how the role of online games in improving math problem-solving abilities (KPM). This research is qualitative research. The analysis was carried out using a case study quantitative approach. The participant involved in this study was an online gamer who was also a doctoral student majoring in Mathematics at the Bandung Institute of Technology (ITB). Participants are also medalists in the astronomy olympiad and are the best graduates of master's degree in mathematics from the University of Indonesia in 2016. Data collection was conducted using email interviews and literacy studies. The data analysis used is based on studies that have been conducted online games play an important role in increasing KPM. Based on the results of the study, through online games, participants have the opportunity to hone their KPM, this is because the stages of problem-solving can be applied in solving unusual online game problems, besides online games, applying mathematical principles in their application.